Two-parametric beam model for dosimetry of the process of electron irradiation of materials with low density and atomic number - Lazurik, V.T.; Lazurik, V.M.; Popov, G.; Zimek, Z. (Вопросы атомной науки и техники, 2021)
The work is devoted to studying the possibility of using a two-parametric model of an electron beam to describe the depth distributions of the electron dose in materials with a low density and an effective atomic number. In this model, the parameters are determined by fitting the semi-empirical model (PFSEM-method) to the results of measurements of the depth-dose distribution in a dosimetric wedge. The depth-dose distributions in a birchwood wedge were measured at the Institute of Nuclear Chemistry and Technology in Warsaw, Poland. The parameters of the electron beam incident on the wedge were determined by the PFSEM method. The Monte Carlo simulations of the depth-dose distribution in the wedge for the process of electron irradiation, the characteristics of which are determined by the PFSEM method, have been carried out. It is shown that there is a satisfactory agreement between the measurement results and the Monte Carlo simulation of the depth-dose distribution. The advantages of describing depth-dose distributions in a wedge based on a two-parametric model of an electron beam in comparison with traditional methods of polynomial approximation of measurement results are discussed.